BF3.Et2O-catalyzed selective C-4 alkylation of isoquinolin1(2H)-ones employing p-quinone methides - More, Devidas A.; Ghotekar, Ganesh S.; Muthukrishnan, M. (Chemistry-an Asian Journal, 2023)
The direct C-4 alkylation of isoquinolin-1(2H)-one moiety is a challenging transformation in organic synthesis. Here we present a practical and efficient synthesis of C-4 alkylated isoquinolin-1(2H)-ones through conjugate addition of isoquinolin-1(2H)-ones to p-quinone methides for the first time. The process is facilitated by Lewis acid catalysis and this operationally straightforward, mild, metal-free and one-pot transformation provides a wide range of C-4 alkylated isoquinolin-1(2H)ones at ambient temperature in good to excellent yields.